The Prevalence, Distribution, and Extent of Subclinical Atherosclerosis and Its Relation With Serum Uric Acid in Hypertension Population - Liu, Fei; Hui, Simei; Hidru, Tesfaldet H.; Jiang, Yinong; Zhang, Ying; Lu, Yan; Lv, Haichen; Lee, Sharen; Xia, Yunlong; Yang, Xiaolei (Frontiers in Cardiovascular Medicine, 2021)
Background: Data are limited on the prevalence, distribution, and extent of subclinical atherosclerosis (SCA) in populations with primary hypertension and an in-depth evaluation is required to explore the impact of elevated serum uric acid (SUA) levels on the systemic extent of SCA. Methods: A total of 1,534 individuals with blood pressure-controlled primary hypertension registered from January 1, 2015 to May 31, 2018 were included. The systemic extent and risk factors of SCA in the carotid, coronary, thoracic, and renal territories were investigated by Doppler ultrasound and computed tomography. Results: SCA was present in 85.9% of patients. The proportion of focal, intermediate and generalized SCA was 17.9, 21.3, and 46.6%. Plaques were most common in the thoracic aorta (74%), followed by the coronary (55.3%), carotid (51.6%), and renal (45.8%) arteries, respectively. Participants were stratified into quartiles based on gender-specific SUA levels. Compared with patients in the first quartile, the Odds Ratio (OR) [95% confidence interval] for SCA in the second, third and fourth quartile were 1.647 (1.011–2.680), 3.013 (1.770–5.124), and 5.081 (3.203–10.496), respectively. Patients with elevated SUA levels at high 10-year Framingham risk had a higher likelihood of a more severe risk of SCA (95.8%). However, extensive SCA was also present in a substantial number of low 10-year-Framingham risk patients at the higher quartiles of SUA (53.8%). Conclusions: SCA was highly prevalent in the hypertension population and the thoracic aorta was the most frequently affected vascular site. Elevated SUA concentration was significantly associated with the prevalence and severity of SCA regardless of territories.